Democracy Does Not Promote Well-Being Except in Rich Countries With Demanding Climates. (September 2014) - Van de Vliert, Evert; Postmes, Tom
Is democracy really a good thing because it improves well-being? Everywhere? Here we use multiple regression analysis to examine continuous associations between democracy and well-being across 137 countries. The results are clarified by breaking them down for 20 poor countries with demanding winters or summers ( threatening habitats ), 48 poor countries with undemanding temperate climates ( unthreatening habitats ), 23 rich countries with undemanding temperate climates ( unchallenging habitats ), and 46 rich countries with demanding winters or summers ( challenging habitats ). We show that democratic governance is negatively related to satisfaction with freedom of choice and overall happiness in threatening habitats and unrelated in unthreatening and unchallenging habitats. Only in challenging habitats of rich countries with demanding climates is democracy positively related to satisfaction with freedom of choice and overall happiness. This pattern of findings, which persists when controlling for a variety of societal risks, might suggest that the link between democracy and well-being can be particularly strengthened by empowering poorer populations in more demanding climates to generate more income.